PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA ASN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA POLRES SITUBONDO - Kamalisa, Dewi; Karnadi, Karnadi; Sari, Lita Permata (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of this study was to analyze the effect of the variable influence of work discipline and work environment on the performance of ASN through work motivation as an intervening variable at the Situbondo Police Office. By using the structural equation model of Partial Least Square (PLS). The result of the direct influence hypothesis test using the Smart PLS 3.0 application Work discipline has a positive but not significant effect on work motivation (H1 is rejected), the work environment has a significant positive effect on work motivation (H2 is accepted), Work discipline has a significant positive effect on ASN performance (H3 is accepted), The Work environment has a positive but not significant effect on ASN Performance (H4 rejected), Work discipline has a positive significant effect on ASN Performance (H5 accepted), Work discipline has a positive but not significant effect on ASN Performance through work motivation (H6 rejected), and the work environment has a significant positiveefeect on the performance of ASN through work motivation (H7 is accepted).